THE ROLE OF PROFESSIONAL IDENTITY IN IMPROVING NURSING SERVICE QUALITY AND JOB SATISFACTION: A LITERATURE REVIEW - Saputra, Dikki; Nabilla, Putri; Intani, Merlisa Kesuma; Fauzan, Suhaimi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Professional identity reflects how nurses perceive and evaluate themselves, shaped by the values, norms, and ethical principles of the nursing profession. This concept encompasses four key aspects: professional values, ethics, knowledge, and leadership. Professional identity contributes to the quality of nursing care and nurses' job satisfaction. This study aims to explore the role of professional identity in these two aspects. A descriptive literature review was conducted to examine the relationship between professional identity, quality of care, and job satisfaction. Following JBI guidelines, the review evaluates nurses’ knowledge, motivation, and practices related to discharge planning. Searches were conducted in PubMed, ScienceDirect, and ProQuest using the keywords